The influence of vacuum mixing on methylmethacrylate liberation from acrylic cement powder - Bettencourt, A (2015)
Polymethylmethacrylate (PMMA) bone cement is a biomaterial used to anchor prostheses during joint replacement surgery. Residual methylmethacrylate monomer (MNA) may be related with the cytotoxic effect of PM MA. The aim of the present paper was to investigate the effect of two different cement mixing methods: hand stirring at atmospheric pressure and under partial vacuum (0.330 and 0.154 bar) on residual monomer liberation in phosphate buffer saline solution from acrylic cement powder. Residual MMA content was determined by high-performance liquid chromatography. Mathematical models were applied to experimental dissolution data revealing that monomer release was significantly reduced in bone cement powder obtained at 0.154 bar vacuum pressure compared to the other mixing conditions. The kinetic models applied are consistent with a simple diffusion mechanism of the monomer from the polymer matrix. (C) 2001 Elsevier Science B.V. All rights reserved.